Study of the effect of storage terms on safety indicators and composition of «Pump powder» biologically active additive - N. N. Kornen; S. A. Kalmanovich; T. A. Shakhray; E. P. Victorova (Новые технологии)
The article presents the results of the study on the effect of shelf life on microbiological safety indicators and composition of «Pumpkin powder» biologically active additive. Domestic scientists and specialists pay special attention to the production of food additives, including those obtained from secondary plant materials, which have not only technological properties, but also corrective and compensatory effects, due to the content of a complex of biologically active macro- and micronutrients in their composition. The aim of the research was to study the effect of shelf life on the microbiological indicators of the safety of the additive, as well as on the change in the additive content of biologically active substances that determine its antioxidant and hepatoprotective properties. It’s been established that the «Pumpkin Powder» additive stored for 12 months at a temperature of 20±2°С and relative air humidity not more than 70%, according to microbiological safety indicators, meets the requirements of ТР ТС 021/2011 «On food products safety». It’s been revealed that during storage of the additive for 12 months with the specified storage modes, the loss of biologically active substances that determine its antioxidant and hepatoprotective properties is insignificant and amounted to: vitamin C - 7%, b-carotene - 8%, P-active substances - 4,5 %. Experiments on laboratory animals have shown that the additive stored for 12 months manifests high antioxidant properties characterized by a decrease in the content of lipid peroxidation products in the blood serum of animals, and hepatoprotective properties, characterized by a decrease in the activity of liver enzymes in the blood serum of animals.